Construction of Oxepino[3,2‐b]indoles via [4+3] Annulation of 2‐Ylideneoxindoles with Crotonate‐Derived Sulfur Ylides - Fei, Xing‐Hai; Zhao, Yong‐Long; Yang, Fen‐Fen; Guan, Xiang; Li, Zong‐Qin; Wang, Da‐Peng; Zhou, Meng; Yang, Yuan‐Yong; He, Bin (Advanced synthesis & catalysis, 2021)
A [4+3] annulation of 2‐ylideneoxindoles with crotonate‐derived sulfur ylides has been developed. A series of oxepino[3,2‐b]indoles were prepared in moderate to excellent yields (62‐93%) under mild conditions. Moreover, the synthetic oxepino[3,2‐b] indoles can be further transformed into more complex cyclopropa[5,6]oxepino[3,2‐b]indoles via a [2+1] cyclopropanation. In addition, the synthetic compounds show certain antiproliferative activity against K562 and MCF‐7 cells, and its IC50 values for these two kinds of tumor cells up to 5.40±0.88 μM and 18.41±0.50 μM, respectively.